The Perspectives to Understand Social Marketing as an Approach in Influencing Consumer Behavior for Good - Iin Mayasari (Gadjah Mada International Journal of Business, 2012)
This study is a conceptual paper and highlights perspectives to understand social marketing as an approach to bring about voluntary and socially desirable consumer behavior. The perspective is considered as an alternative way to comprehend consumer behavior change for good as a multi-factor driven action. Hence, social marketing is also considered as a discipline that can be analyzed from multiple perspectives including a behavioral change perspective and a relationship perspective. Each perspective is elaborated by doing a review of existing literature and research. This study shows that social marketing is not only the application of marketing programs to shape consumer behavior, but also a process involving individual, society, and government to make a better life of society.